Public-private sector partnership in economic development : a case for Sri Lanka - Indraratna, A. D. V. de S.; Sri Lanka Economic Association. Session 2005 : Colombo, Sri Lanka); Indraratna, A. D. V. de S.; Ranasinghe, Athula, 1959-; Sri Lanka Economic Association (Colombo : Sri Lanka Economic Association, 2006)
Contributed papers presented as 6th Annual Session of Sri Lanka Economic Association held on 15-16 July 2005 at Colombo.
Keywords: Public-private sector cooperation -- Sri Lanka -- Congresses; Sri Lanka -- Economic policy -- Congresses